PENYULUHAN PENGANEKA-RAGAMAN JENIS KEMASAN, LEBEL DAN MEREK BAGI PENGRAJIN OLAHAN SINGKONG DI DESA SITIHARJO KABUPATEN MUSI RAWAS - Vera Octalia; Ira Primalasari (LP4MK STKIP PGRI Lubuklinggau, 2023)
The purpose of this PKM activity is to increase knowledge, skills, and change people's mindsets regarding packaging and labeling techniques for processed cassava products. The service activity was carried out by providing counseling to processed cassava craftsmen in Sitiharjo Village, Tugumulyo District about the importance of good and attractive packaging. Good and attractive packaging and informative labeling will increase buyer interest in the products offered either for self-consumption or as souvenirs. Good packaging will increase the added value of the product which in turn supports the sustainability of the cassava processing business and increases better income.